Marie-Antoinette : la reine refusée - Christine Dousset (Les Cahiers de Framespa)
Queen Marie-Antoinette has suffered increasing unpopularity from the beginning of her reign in 1775 until her death in 1793. Many critics were made against her : reject of the « étiquette », luxury, lust, her strong and bad political influence upon the king, her attachment to Austria. All of them are political and reveal new questions and expectations of the body politic : crisis of the system of representation of royal power, affirmation of a new sovereignty and of the principle of equality, reject of the possibility for women to access to power and political sphere, birth of Nation and patriotism. An imaginary Marie-Antoinette has acted as a foil to allow French people to challenge the legitimacy of monarchy.